2021
DOI: 10.3390/ijerph182111149
|View full text |Cite
|
Sign up to set email alerts
|

When Does a Lot Become Too Much? A Q Methodological Investigation of UK Student Perceptions of Digital Addiction

Abstract: Despite the benefits of the internet and other digital technology, the online world has been associated with a negative impact on university student wellbeing. Many university students report symptoms of pathological internet use. Internationally, further research is needed to understand what student users of technology perceive to be problematic internet and/or digital use. The current study explores the range of perceptions that university students hold about ‘digital addiction’. We recruited 33 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…People are often unaware of when their technology and/or online use becomes problematic [ 37 , 38 ], suggesting that increasing awareness might be important. Until very recently, there had been no evaluation of the impact of offering feedback on problematic smartphone use.…”
Section: Discussionmentioning
confidence: 99%
“…People are often unaware of when their technology and/or online use becomes problematic [ 37 , 38 ], suggesting that increasing awareness might be important. Until very recently, there had been no evaluation of the impact of offering feedback on problematic smartphone use.…”
Section: Discussionmentioning
confidence: 99%
“…Time spent on digital devices is positively linked to digital addiction [29]. Digital addiction is associated with psychological health issues like anxiety, depression, and social isolation, as individuals often use digital devices to cope with negative emotions [30]. This study contributes to our understanding of digital media addiction by exploring its prevalence among college students and examining its effects on variables such as body shape dissatisfaction, time spent on digital devices, and psychological health.…”
Section: Introductionmentioning
confidence: 98%
“…Different digital tools, and in particular the internet, have transformed the way young people live, learn, interact and participate in society. As the constant use and carrying of digital devices has become a social norm, people often do not realise that they may be experiencing symptoms of digital device overuse (Turner et al, 2021). Studies have shown that excessive use of digital devices over a prolonged period of time can lead to behavioural addiction (Chen et al, 2020;Kesici & Tunç, 2018), similar to other addictive disorders (Joseph & Hamiliton-Ekeke, 2016), developing as a result of habit formation and self-control problems (Allcott et al, 2022).…”
Section: Introductionmentioning
confidence: 99%